Real time detection of phishing websites - Ahmed, Abdulghani Ali; Nurul Amirah, Abdullah (IEEE, 2016)
Resinification of liquefied empty fruit bunch with furfural (LEFB-Fu) was performed. During the resinification process, the samples were taken every hour up to 4 hours. FTIR analysis of the samples was conducted to understand the progress of the reaction. It showed that the bands of 1512 cm−1 and 1692 cm−1 evolving and diminishing respectively, indicating the consumption of furfural. The postulation of polymerization was also proven as the increasing extent of substitution of aromatic ring observed.